Interpersonal threat sensitivity in borderline personality disorder: an eye-tracking study - Bertsch, Katja; Krauch, Marlene; Stopfer, Katharina; Herpertz, Sabine (Journal of personality disorders, 2017)
Threat sensitivity is a prominent predictor of interpersonal dysfunctions in borderline personality disorder (BPD), leading to intense, aversive feelings of threat and eventually dysfunctional behaviors, such as aggression. In the present study, BPD patients and healthy volunteers classified angry, fearful, neutral, and happy faces presented for 150 ms or 5,000 ms to investigate initial saccades and facial scanning. Patients more often wrongly identified anger, responded slower to all faces, and made faster saccades towards the eyes of briefly presented neutral faces and slower saccades away from fearful eyes compared with healthy volunteers. Latency of initial saccades and fixation duration correlated negatively with the patients’ aggressiveness. Supporting previous results, BPD patients did not experience general deficits in facial emotion processing, but a specific hypersensitivity for and deficits in detailed evaluation of threat cues, which was particularly enhanced in aggressive patients. Interventions might benefit from relocating attention towards positive information and detailed evaluation of social cues.